Świat wartości w czasopiśmie "Polonistyka" w latach 1948-1956 = World of values in the periodic "Polish philology" years 1948-1956 - Seul, Anastazja (1961- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents forced on teachers and students system of values acceptable during first years of socialistic regime in Poland. The axiology of Marxism`s ideologists was entirely different form the one that formed Polish culture over the ages. This periodic intended to form teachers of Polish language many times presented articles on ideology that was to form Polish system of values such as: "socialistic worldview of life", "socialistic morality", war against the Church, friendship with CCCR and other socialist countries compared with hostility of capitalistic countries, to name a few.
Keywords: "Polonistyka" - czasopismo; socjalistyczny system wartości; personalizm; marksizm; Jan Paweł II, papież (1929-2005); ideologia a nauka; socialistic system of values; personalism; Marxism; John Paul II; ideology vs science